2001
DOI: 10.1079/pns200059
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of genetic change in farm animals on food intake and feeding behaviour

Abstract: Selection in commercial populations on aspects of output, such as for growth rate in poultry, against fatness and for growth rate in pigs, and for milk yield in cows, has had very large effects on such outputs over the past 50 years. Partly because of the cost of recording intake, there has been little or no selection for food intake or feeding behaviour. In order to predict the effects of such past, and future, selection on intake it is necessary to have some suitable theoretical framework. Intake needs to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 49 publications
(81 reference statements)
4
46
0
1
Order By: Relevance
“…Although all these models recognize the need for genetically driven trajectories (either explicitly or implicitly), they do not invoke (physiological state dependent) genetic expression, but instead use time as the driver to generate the homeorhetic trajectories. This may seem like a detail, but studies of growth have shown that relating trajectories to measures of physiological state, for example, degree of maturity, greatly extends the ability of models to accommodate genotype differences (Taylor, 1980;Emmans and Kyriazakis, 2001;Doeschl-Wilson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although all these models recognize the need for genetically driven trajectories (either explicitly or implicitly), they do not invoke (physiological state dependent) genetic expression, but instead use time as the driver to generate the homeorhetic trajectories. This may seem like a detail, but studies of growth have shown that relating trajectories to measures of physiological state, for example, degree of maturity, greatly extends the ability of models to accommodate genotype differences (Taylor, 1980;Emmans and Kyriazakis, 2001;Doeschl-Wilson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…where P maint is maintenance P requirements (g/day), p is a coefficient (g/day) expected to be constant across pig genotypes (Emmans and Kyriazakis, 2001), Pr is the pig actual body protein weight (kg) and Pr m is its protein content at somatic maturity (kg).The value of p was estimated to be 0.1293 (g/day) from the data of Jongbloed (1987), by making the following assumptions: (i) the relationship between Pr and body weight (BW) is allometric (Whittemore et al, 1988) and (ii) the Pr m of the crossbred Dutch Landrace × Dutch Yorkshire gilts used was 30 kg (Knap 2000). The advantages of equation (2) over existing estimates of P maint are that it can be applied across pig sizes and genotypes, and account for genetic change.…”
Section: Prediction Of Food Intakementioning
confidence: 99%
“…The initial state of the pig was described by its initial body weight (BW0), from which the chemical composition of the pig was calculated assuming that the pig had its ideal composition set by its genotype (Emmans and Kyriazakis, 2001). The potential rate of protein retention was determined by pig phenotype and current protein weight only.…”
Section: Methodsmentioning
confidence: 99%
“…The protein and lipid growth of a certain pig phenotype can be described by a Gompertz function with the following parameters (representing growth traits): protein content at maturity (Pr m , kg), lipid content at maturity (L m , kg) and the relative growth rate at the inflection point of the growth curve (B, day − 1 ), in accordance with Ferguson et al (1997), Knap (2000), Emmans and Kyriazakis (2001), Pomar et al (2003) and Wellock et al (2004): dPr=dt ¼ Pr B lnðPr m =PrÞ kg=day; and dL=dt ¼ L B lnðL m =LÞkg=day Strategies to decrease P excretion by pigs where Pr and L are the body protein and lipid contents (kg), respectively.…”
Section: Generating Variation In Pig Growthmentioning
confidence: 99%